West Syndrome Is an Exceptional Presentation of Pyridoxine- and Pyridoxal Phosphate-Dependent Epilepsy: Data From a French Cohort and Review of the Literature - Gibaud, Marc; Barth, Magalie; Lefranc, Jérémie; Mention, Karine; Villeneuve, Nathalie; Schiff, Manuel; Maurey, Hélène; Barthez, Marie-Anne; Caubel, Isabelle; Chouchane, Mondher; Doummar, Diane; Kossorotoff, Manoëlle; et al. (Frontiers in Pediatrics, 2021)
Objective: To characterize the electro-clinical presentation of patients with pyridoxine-dependent epilepsy (PDE) and pyridoxal phosphate (PLP)-dependent epilepsy in order to determine whether some of them could be diagnosed as de novo West syndrome, i. e., West syndrome that starts after the age of 2 months without other types of seizures (focal seizures for instance) before the onset of epileptic spasms. Methods: We analyzed data from an unpublished cohort of 28 genetically confirmed cases of PDE with antiquitine (ATQ) deficiency and performed a review of the literature looking for description of West syndrome in patients with either PDE with ATQ deficiency or PLP-dependent epilepsy with Pyridox(am)ine phosphate oxidase (PNPO) deficiency. Results: Of the 28 cases from the ATQ deficiency French cohort, 5 had spasms. In four cases, spasms were associated with other types of seizures (myoclonus, focal seizures). In the last case, seizures started on the day of birth. None of these cases corresponded to de novo West syndrome. The review of the literature found only one case of PNPO deficiency presenting as de novo West syndrome and no case of ATQ deficiency. Significance: The presentation of PDE- and PLP-dependent epilepsy as de novo West syndrome is so exceptional that it probably does not justify a systematic trial of pyridoxine or PLP. We propose considering a therapeutic trial with these vitamins in West syndrome if spasms are associated with other seizure types or start before the age of 2 months.